Binge ethanol exposure increases the Krüppel-like factor 11-monoamine oxidase (MAO) pathway in rats: Examining the use of MAO inhibitors to prevent ethanol-induced brain injury. (June 2016) - Duncan, Jeremy W.; Zhang, Xiao; Wang, Niping; Johnson, Shakevia; Harris, Sharonda; Udemgba, Chinelo; Ou, Xiao-Ming; Youdim, Moussa B.; Stockmeier, Craig A.; Wang, Jun Ming
Abstract: Binge drinking induces several neurotoxic consequences including oxidative stress and neurodegeneration. Because of these effects, drugs which prevent ethanol-induced damage to the brain may be clinically beneficial. In this study, we investigated the ethanol-mediated KLF11-MAO cell death cascade in the frontal cortex of Sprague–Dawley rats exposed to a modified Majchowicz 4-day binge ethanol model and control rats. Moreover, MAO inhibitors (MAOIs) were investigated for neuroprotective activity against binge ethanol. Binge ethanol-treated rats demonstrated a significant increase in KLF11, both MAO isoforms, protein oxidation and caspase-3, as well as a reduction in BDNF expression in the frontal cortex compared to control rats. MAOIs prevented these binge ethanol-induced changes, suggesting a neuroprotective benefit. Neither binge ethanol nor MAOI treatment significantly affected protein expression levels of the oxidative stress enzymes, SOD2 or catalase. Furthermore, ethanol-induced antinociception was enhanced following exposure to the 4-day ethanol binge. These results demonstrate that the KLF11-MAO pathway is activated by binge ethanol exposure and MAOIs are neuroprotective by preventing the binge ethanol-induced changes associated with this cell death cascade. This study supports KLF11-MAO as a mechanism of ethanol-induced neurotoxicity and cell death that could be targeted with MAOI drug therapy to alleviate alcohol-related brain injury. Further examination of MAOIs to reduce alcohol use disorder-related brain injury could provide pivotal insight to future pharmacotherapeutic opportunities. Highlights: The Krüppel-like factor 11-monoamine oxidase (KLF11-MAO) pathway is activated by binge ethanol exposure. Monoamine oxidase inhibitors (MAOIs) demonstrate neuroprotection by preventing binge ethanol-induced changes. Binge ethanol enhances markers of cell death/dysfunction such as caspase-3 and protein oxidation.